Intellectual Capital Disclosure in Determining the Economic Value Added Spread of Service Companies in Indonesia - Hatane, Saarce Elsye; Tarigan, Josua; Zanderet’s, Christina (Universitas Pendidikan Indonesia, 2019)
Abstract. This study aims to observe the of intellectual capital disclosure on ECONOMIC VALUE ADDED (EVA) Spread. The study is conducted at a service industry sector, listed on the Indonesia Stock Exchange in the 7 years observation period, 2010 to 2016. This study examines 427 firm years from 61 companies. Human Capital Disclosure (HCD), Relational Capital Disclosure (RCD) and Structural Capital Disclosure (SCD) are used to measure intellectual capital disclosure as the independent variables. Another independent variable is Return on Assets (ROA), return on equity (ROE) and Operating Cash Flow Ratio (OCF-R) which are used to measure profitability. EVA spread is the dependent variable. There are two control variables used are firm size and firm age. In total there are six hypotheses to be tested in this study. Data testing is done using Gretl software. The results of this study are quite diverse. Five of the six independent variables have no significant effect on EVA Spread. On the other hand, SCD has a significant positive effect on EVA SpreadKeywords. Intellectual Capital Disclosure, Human Capital Disclosure, Relational Capital Disclosure, Structural Capital Disclosure, Profitability, EVA Spread.